2022
DOI: 10.1214/21-aoas1511
|View full text |Cite
|
Sign up to set email alerts
|

Identifying intergenerational patterns of correlated methylation sites

Abstract: DNA methylation can be transmitted through generations. This paper proposes a clustering method to identify the intergenerational patterns from parents to their offspring. Motivated by the potential of correlation between DNA methylation sites, we use the multivariate generalized beta distribution to model the blockwise correlation structure among the sites. A stochastic EM algorithm is implemented to estimate the parameters, and BIC is applied to determine the optimal number of clusters. Simulations demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Other epigenetic factors may also be passed in sperm, such as non‐coding RNAs and retained histones. 12 Recent epidemiological studies based on probabilistic models examined and supported intergenerational epigenetic inheritance, 13 , 14 where it was shown that at some CpG sites, the association of DNA methylation between mothers and offspring was stronger compared to the association between fathers and offspring. The number of CpGs with fathers being dominant in DNA methylation transmission is much smaller.…”
Section: Epigenetic Transfer Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other epigenetic factors may also be passed in sperm, such as non‐coding RNAs and retained histones. 12 Recent epidemiological studies based on probabilistic models examined and supported intergenerational epigenetic inheritance, 13 , 14 where it was shown that at some CpG sites, the association of DNA methylation between mothers and offspring was stronger compared to the association between fathers and offspring. The number of CpGs with fathers being dominant in DNA methylation transmission is much smaller.…”
Section: Epigenetic Transfer Of Informationmentioning
confidence: 99%
“… 61 Data analyses in transgenerational epigenetic research mainly focus on DNA methylation transmission from one generation to the next and transgenerational association studies. 13 , 14 , 67 , 68 Further development of multiple‐exposure, multiple‐mediator and multiple‐outcome framework in studies of multi‐generational epigenetic inheritance is needed.…”
Section: Data Analysis In Epigenetic Research and Critical Review Of ...mentioning
confidence: 99%
“…Generalized beta distribution fits the definition of DNAm defined as beta values, and in addition, accounts for the correlation structures among adjacent CpG sites. It has been used to model the distribution of nominal family income and stock indexes in economics [ 21 ] and to identify the intergenerational patterns of DNAm levels [ 22 ] in the epigenetic study.…”
Section: Introductionmentioning
confidence: 99%